Karakteristik Pasien Rhinitis di Rumah Sakit Umum Daerah Tabanan - Putu Surya Nandana; Agus Santosa; Ni Wayan Sri Ekayanti; Saraswati Laksmi Dewi; Gita Ratnasari; Diana Sudan (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Rhinitis is one of the upper respiratory tract disorders with a continuously increasing global prevalence. Although it is considered a common condition, the characteristics of rhinitis patients vary across regions and are influenced by demographic, environmental, and genetic factors. This study aimed to describe the characteristics of patients with rhinitis at RSUD Tabanan during 2020–2023, based on age group, sex, family history of atopy, and main clinical complaints. This study employed a descriptive, cross-sectional design, using retrospective data from the medical records of patients attending the otorhinolaryngology outpatient clinic. The sampling technique used was non-probability sampling with a total sampling method. Data analysis was performed univariately and presented as frequency distribution tables. The results showed that the 10–19-year age group was the most common (24.6%), the majority of patients were male (62.3%), most patients had no history of atopy (92.8%), Tabanan District was the area with the highest number of cases (23.2%), which may be influenced by the location of RSUD Tabanan in Tabanan District, and the main presenting complaint was nasal obstruction (66.7%). This study provides an overview of the characteristics of patients with rhinitis at Tabanan Regional General Hospital, which is expected to serve as a basis for improving diagnostic accuracy and planning more effective management and preventive strategies. Keywords: Allergic Rhinitis, Non-Allergic Rhinitis, Patient Characteristics, Clinical Complaints.  ABSTRAK Rhinitis merupakan masalah kesehatan global akibat morbiditas yang ditimbulkan. Meskipun tergolong umum, karakteristik pasien rhinitis bervariasi di setiap wilayah, dipengaruhi oleh faktor demografis, lingkungan, dan genetik. Penelitian ini bertujuan untuk mengetahui karakteristik pasien rhinitis di RSUD Tabanan selama periode tahun 2020-2023 berdasarkan kelompok usia, jenis kelamin, riwayat atopi dalam keluarga, dan keluhan klinis utama. Penelitian ini menggunakan desain deskriptif dengan pendekatan potong lintang (cross-sectional), serta data diperoleh secara retrospektif melalui rekam medis pasien poliklinik THT. Teknik pengambilan sampel menggunakan metode non-probability sampling jenis total sampling. Analisis data dilakukan secara univariat dan disajikan dalam bentuk tabel distribusi frekuensi. Hasil penelitian menunjukkan bahwa kelompok usia 10-19 tahun merupakan yang terbanyak (24,6%), jenis kelamin terbanyak adalah laki-laki (62,3%), sebagian besar pasien tidak memiliki riwayat atopi (92,8%), Kecamatan Tabanan tercatat sebagai wilayah dengan proporsi kasus tertinggi (23,2%), yang dipengaruhi oleh lokasi RSUD Tabanan yang berada di Kecamatan Tabanan, dan keluhan utama pasien yaitu hidung tersumbat (66,7%). Karakteristik yang teridentifikasi menunjukkan pentingnya pendekatan yang lebih spesifik dalam penanganan rhinitis, terutama pada kelompok usia remaja dan laki-laki. Kata Kunci: Rhinitis Alergi, Rhinitis Non-Alergi, Karakteristik Pasien, Keluhan Klinis.